Avaliação dos efeitos da hidroxiapatita e do resveratrol sobre o tecido ósseo de ratos contaminados com acetato de chumbo - Pastor, Fabio Alexandre Casarin (2013)
Lead (Pb) is an ubiquitous pollutant in the environmental ecosystem. Its distribution is mainly anthropogenic, coming from the burning of fossil fuels, mining and production of various industrial products. There is little knowledge of the effect of the Pb and its compounds on bone metabolism as well as potential therapies for frames contamination related to the lead. The aim of this study was to determine possible changes in the bones of adult rats contaminated with lead acetate correlated them to the effects of hydroxyapatite and the resveratrol in adult rats contaminated with lead acetate. The biomechanical, biometric, biophysical, microtomographic bone parameters, the radiographic density, the concentration of Pb and metalloproteinase activity in bone tissue were analyzed. The animals were distributed into 6 groups of 8 rats each: control, treated with saline 0.9% (0.1 ml/100g BM), hydroxyapatite, treat with hydroxyapatite (100 mg/kg BM), contaminated, treated with lead acetate (250 mg/kg BM), contaminated + hydroxyapatite, treated with lead acetate (250mg/kg BM) and hydroxyapatite (100mg/kg BM); the treatments were carry out once per week for 8 weeks by gastric gavage. The groups contaminated + resveratrol, treated with lead acetate (250 mg/kg BM) and resveratrol (0.7 mg/kg BM ) and DMSO, treated with dimethylsulfoxide (0.1 ml/100g BM), 5 times a week for 8 weeks by intraperitoneal injections. The contamination with lead acetate promoted incorporation of it in bone tissue leading to a reduction in bone strength of femurs and vertebrae, reduction of vertebral trabecular contingent, and increased activity of metalloproteins type 2. The treatment with hydroxyapatite (100 mg/kg MC) as well with resveratrol (0.7 mg/kg MC) prevented the deleterious effects of lead contamination at the proposed dose, including reducing the activity values of metalloproteins type 2 to levels similar to that of control group. Therefore, the results point to hydroxyapatite and resveratrol as potential treatment agents in lead contamination, preventing damage to the quality of bone tissue caused by this element.